Diagnostic and predictive value of N: L ratio for severity of acute appendicitis - Somnath Biswas; Indranil Halder; Mintu Mohan Nandi; Shanmugam Karthick; Mohan Pradhan (Asian Journal of Medical Sciences)
Background: The most frequent surgical emergency in clinical practice is acute appendicitis (AA), which has a lifetime incidence of about 7% per person. In the past, appendectomy was the gold standard for treating AA; however, in recent years, this conventional paradigm of therapy has faced significant challenges.